A parallel genetic algorithm for the geometrically constrained site layout problem - Zouein, P. (2018)
Parallel genetic algorithms techniques have been used in a variety of computer engineering and science areas. This paper presents a parallel genetic algorithm to solve the geometrically constrained site layout problem that involves coordinating the use of limited space to accommodate temporary facilities subject to geometric constraints. The algorithm is parallelized based on a message passing architecture using parallel search and chromosomes migration. The algorithm is tested on a variety of layout problems to illustrate its performance and many favorable results are reported.